How can grain price support policies enhance stable and increased wheat production? A risk aversion and cost saving perspective - Chen, Sisi; Li, Guangsi (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe food price support policy aimed at stability has become a key strategy for safeguarding food security. Since its implementation, wheat production in China has seen significant growth. However, the economic benefits from wheat farming have not increased in tandem, leading to the phenomenon of “increased production without increased income”. As a result, the effects of food price support policies on wheat production and the incentive mechanisms driving this change remain insufficiently studied.MethodsThis paper provides a comprehensive theoretical and empirical analysis of how food price support policies influence the incentive mechanisms driving wheat production, focusing on the mediating role of farmers' decision-making behavior. Based on Schultz's “rational man” principle of self-utility maximization, and from the perspectives of risk-sharing and cost-saving, the study divides the incentive mechanisms guiding farmers' production decisions into three areas: price stabilization, income stabilization, and comprehensive cost savings. Meanwhile, empirical connections between price support policies, farmers' decision-making, and wheat production are examined. Empirical tests are conducted using provincial panel data from 15 major wheat-producing provinces in China (2000–2021), employing dynamic difference-in-differences and mediation effect models.ResultsThe study shows that the price support policy has significantly boosted wheat production. Dynamic effect analysis indicates that the policy has a short-term impact on improving wheat yield. Regional heterogeneity analysis reveals that provinces respond differently to the policy, with varying levels of sustainability in the increased wheat production. This variation is mainly due to differences in agricultural resource distribution and cropping structures across regions. Mechanism analysis suggests that the policy effectively incentivizes wheat production by stabilizing market price fluctuations, ensuring stable farmer income, and reducing overall production costs.DiscussionBased on the above findings, it is recommended that, while continuing to implement the price support policy, more targeted policy adjustments be made to reflect the specific characteristics of different regions. Additionally, strengthening agricultural infrastructure, establishing diversified income subsidy mechanisms for farmers, and optimizing production input structures are essential for enhancing the long-term effectiveness and sustainability of the policy. The results of this study have important implications for policymakers, agricultural managers, and researchers, providing insights into improving sustainable food production in China and other regions with similar contexts.